Lactide-caprolactone copolymers with tuneable barrier properties for packaging applications. (12th August 2020) - Sangroniz, Ainara; Sangroniz, Leire; Hamzehlou, Shaghayegh; Río, Javier del; Santamaria, Antxon; Sarasua, Jose Ramon; Iriarte, Marian; Leiza, Jose Ramon; Etxeberria, Agustin
Abstract: Lactide-caprolactone copolymers have been synthetized employing two metallic catalysts, Ph3 Bi and SnOct2 . The analysis of the microstructure by NMR reveals that gradient like copolymers are obtained with SnOct2 catalyst, whereas for Ph3 Bi based copolymers the gradient like character is less pronounced. The incorporation of caprolactone reduces the crystallinity degree and the glass transition temperature, leading to a slight increase of the free volume fraction. Thermal properties, free volume fraction and chemical nature of the penetrant are correlated with obtained oxygen and water vapour permeability. It is demonstrated that selecting adequate compositions of lactide-caprolactone copolymers it is possible to broaden the field of biodegradable polymers in packaging applications. Graphical abstract: Image 1 Highlights: Gradient lactide-caprolactone copolymers have been synthetized. The incorporation of caprolactone reduces drastically the T g and crystallinity. Addition of caprolactone does not alter the free volume or the rheological properties. The copolymers show good water barrier properties and moderate oxygen permeability. Permeability is correlated with free volume, T g and penetrant-polymer interactions.